Giordano Bruno y la revolución social, política y teológica de un universo infinito - Flantrmsky Cárdenas, Óscar (2022)
This paper analyzes the social, political and theological implications proposed by Giordano Bruno, based on his proposal for an infinite universe. For this, the concepts of emptiness and plurality, that allow the understanding of the infinite universe model, explained in a second moment, will be analyzed in order to offer an analysis of the relationship of this proposal with a revolutionary thought in the social, political and theological field of the 16th century.